THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF TEACHING MATHEMATICS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Atabaeva, Baxıtlı Jaxanshaevna; Davlatbayeva, Xolida Nodirbekovna (SCIENCE and SOCIETY, 2026)
This article identifies and systematizes the theoretical and methodological foundations of teaching mathematics in a digital learning environment. The study aims to substantiate mechanisms for developing mathematical competences within digital didactics, to describe the methodological transformation of teachers’ practice, and to justify reliability-oriented principles of digital assessment.